Assessing the Influence of Butter-Substitution with Margarine in Sorbitol and Sucrose Cereal Bar Base: Taste, Texture, and Aroma Evaluation by Consumer Preference - Angrainy, Hanny; Chandra, Thalia; Anjali, Cailin; Utama, Nicholas Kevin (Indonesian Journal of Life Sciences, 2023)
A B S T R A C T Taste, texture, and aroma are fundamental sensory properties in influencing consumer liking of cereal bars. The majority of consumers ranked ‘taste’ as the most important characteristic influencing their purchase intent, followed by textural and aroma features which define the product quality and acceptability. Butter is a major component in cereal bars, and plays an important role in its sensorial properties, however butter is expensive and not vegan friendly. Margarine is often used to substitute butter due to the cost and increasing trend of plant-based. This research aimed to study the eﬀect of butter substitution with margarine in sorbitol and sucrose cereal bar towards consumer preference on taste, texture, and aroma. Four types of samples: sucrose-butter, sucrose-margarine, sorbitol-butter, and sorbitol-margarine were examined using triangle and 9-scale hedonic tests among 50 panelists. Results of this study showed that the substitution of butter with margarine in sucrose cereal bars were found to have a significant difference on various attributes, including firmness, chewiness, taste, and aroma. Furthermore, for the ranking test, the most preferred samples were butter-sorbitol and margarine-sucrose cereal bar base with similar proportion, which is 38% of participants. While the least favorite sample was butter-sucrose with 64% of panelists choosing the samples. This indicates that different combination ingredients can provide high consumer product acceptance for a cereal bar and can be used to develop a butter substitute cereal bar product desirable for the consumer market.